Atrial Repolarization Waves (Ta) Mimicking Inferior Wall ST Segment Elevation Myocardial Infarction in a Patient with Ectopic Atrial Rhythm - Janaki Rami Reddy Manne (Case Reports in Medicine)
We present a case of atrial repolarization waves from an ectopic atrial rhythm mimicking inferior ST segment elevation myocardial infarction in a 78-year-old male patient who presented with left sided chest wall and shoulder pain. His ischemic workup was negative, and the ST elevations completely resolved upon the resumption of sinus rhythm before discharge.